Development and Performance Evaluation of a Novel Ancestry Informative DIP Panel for Continental Origin Inference - Zhou, Yongsong; Jin, Xiaoye; Wu, Buling; Zhu, Bofeng (Frontiers in Genetics, 2022)
Ancestry informative markers (AIMs) are useful to infer individual biogeographical ancestry and to estimate admixture proportions of admixed populations or individuals. Although a growing number of AIM panels for forensic ancestry origin analyses were developed, they may not efficiently infer the ancestry origins of most populations in China. In this study, a set of 52 ancestry informative deletion/insertion polymorphisms (AIDIPs) were selected with the aim of effectively differentiate continental and partial Chinese populations. All of the selected markers were successfully incorporated into a single multiplex PCR panel, which could be conveniently and efficiently detected on capillary electrophoresis platforms. Genetic distributions of the same 50 AIDIPs in different continental populations revealed that most loci showed high genetic differentiations between East Asian populations and other continental populations. Population genetic analyses of different continental populations indicated that these 50 AIDIPs could clearly discriminate East Asian, European, and African populations. In addition, the 52 AIDIPs also exhibited relatively high cumulative discrimination power in the Eastern Han population, which could be used as a supplementary tool for forensic investigation. Furthermore, the Eastern Han population showed close genetic relationships with East Asian populations and high ancestral components from East Asian populations. In the future, we need to investigate genetic distributions of these 52 AIDIPs in Chinese Han populations in different regions and other ethnic groups, and further evaluate the power of these loci to differentiate different Chinese populations.